Abscisic acid: Metabolism, transport, crosstalk with other plant growth regulators, and its role in heavy metal stress mitigation - Kumar, Sandeep; Shah, Sajad Hussain; Vimala, Yerramilli; Jatav, Hanuman Singh; Ahmad, Parvaiz; Chen, Yinglong; Siddique, Kadambot H. M. (Frontiers in Plant Science, 2022)
Heavy metal (HM) stress threatening agricultural crops, ecological systems and human health worldwide. HM toxicity adversely affects plant growth, physiological processes and crop productivity by disturbing cellular ionic balance, metabolic balance, cell membrane integrity and protein and enzyme activities. Plants under HM stress intrinsically develop mechanisms to counter the adversities of HM but not prevent them fully. However, the exogenous application of abscisic acid (ABA) is a strategy for boosting the tolerance capacity of plants against HM toxicity by improving the osmolyte accumulation and antioxidant machinery of plants. ABA is an essential plant growth regulator that modulates various plant growth and metabolic processes, including seed development and germination, vegetative growth, stomatal regulation, flowering and leaf senescence under diverse environmental conditions. This review summarizes the ABA biosynthesis, signaling, transport and catabolism in plant tissues and the negative impacts of HM stress on crop plants. Moreover, we also describe the role of ABA in HM stress mitigation and elucidate the interplay of ABA with other plant growth regulators.